Synergy Organizational Structure Design Based on the Values of Gentleness, Deliberation, and Trust in Surah Ali Imran Verse 159 - Sumanja, Kibar; Supiyatul Hikmat, Yayat; Rumuar, Yusran; Utama, Rony Edward (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
Changes in the modern workplace require organizations to not only rely on efficiency and productivity, but also balance humanitarian, moral, and spiritual values ​​as a solid ethical foundation. This study aims to examine the Qur'anic values ​​in Surah Ali Imran verse 159, specifically rahmah (gentleness), shura (deliberation), and tawakal (spiritual trust), and their relevance in building a synergistic organizational structure design. This study uses a descriptive qualitative approach through the thematic interpretation method (maudhu'i), supported by a literature analysis of modern management literature and Islamic leadership studies. The results show that the value of rahmah plays a role in shaping humanistic and empathetic emotional leadership; shura creates a participatory and collaborative decision-making mechanism; while tawakal strengthens spiritual resilience that supports organizational adaptation in facing the dynamics of change. These three values ​​synergize to form a more adaptive, inclusive, and civilized organizational structure framework, so that it does not only focus on material achievements but also facilitates character development and blessings in organizational activities. This study proposes a spiritual synergy model as a new paradigm for management based on Qur'anic values ​​that is relevant for addressing global challenges and building sustainable organizations.